Systemic lupus erythematosus presenting as atypical erythema multiforme-like lesions: a diagnostic challenge - Xiaojing Hu; Fen Liu; Juanjuan Zong (BMC Oral Health)
Abstract Objectives Systemic Lupus Erythematosus (SLE) can cause oral mucosal lesions, it is a severe autoimmune disease, manifesting as variable kinds of oral lesions. Occasionally, these clinical manifestations maybe be misdiagnosed as other diseases. The aim of the present article is to report a rare case of SLE oral mucosa lesions masquerading as an Erythema multiforme (EM) oral lesions in a young man. Case presentation A 34-year-old man with acutely oral lesions for about 10 days, presenting as diffusely oral mucosal hyperemia, erosions and ulcerations. The history, the clinical manifestations of the oral mucosal lesions, palms erythematous plaques and painless target lesions, lower limbs painless erythema and laboratory tests results were comprehensively considered. Finally the case was diagnosed as SLE. Conclusions The report of EM-like oral mucosal lesion of SLE is an extremely rare finding. In the diagnosis of SLE or EM, it is important to consider the history, clinical information and hematological examination. Sometimes histopathology and immunofluorescence are necessary.